A Development of Health Behavior Promotion Program of Primary Hypertensive Patients - เจริญพงศ์ ชวนพิศ; นิติธรรม อลิสา; ธีรเวชเจริญชัย สุพัฒน์; เฉลยกิตติ สายสมร (Journal of The Royal Thai Army Nurses, 2019)
This quasi-experimental research two groups pretest-posttest design aimed to develop Health Promotion Behaviors Program of the primary hypertensive patients. The samples consisted of 60 female hypertensive patients attended at Health Promoting Hospital,Tum-bon Dong la-kon, Muang District, Nakhon Nayok. The samples were divided into two groups, 30 patients each. One group was experimental group and the other one was control group. The instrument used in this study was the Health Promotion behavior Program. Data were collection by using questionnaires of disease knowledge, self-efficacy, health believe model, social support and health behavior which verified for content validity by a panel of five experts. The reliability was presented at .93, .88, .93,.92and.94 respectively.Blood pressure was monitoring before and after implementing the program. Data were analyzed by Descriptive statistics,t-test and independent t-test. The results showed that after implementing the program, the experimental group had better average score than pre-test and control group and had lower blood pressure-level than pre-test and control group at statistically significant level of .05.